In vitro ACE-inhibitory peptide KGYGGVSLPEW facilitates noradrenaline release from sympathetic nerve terminals: relationship with the lack of antihypertensive effect on spontaneous hypertensive rats - Marques, Cláudia (2016)
This study aimed to validate the antihypertensive activity of the angiotensin-converting enzyme (ACE)-inhibitor whey protein hydrolysate (WPH) obtained through the action of proteolytic enzymes fromCynara Cardunculus. The antihypertensive activity of WPH fractions containing peptides with molecularweight below 3 kDa (Whey < 3 kDa) and 1 kDa (Whey < 1 kDa) along with the antihypertensive activity ofthree potent ACE-inhibitory peptide sequences (DKVGINYW, DAQSAPLRVY and KGYGGVSLPEW), previ-ously identified in WPH, were also investigated. In parallel, the influence of KGYGGVSLPEW (the mostpotent ACE-inhibitory peptide sequence) on AT1receptors (a common pharmacological target of anti-hypertensive therapies beyond ACE), was evaluated. The effect of WPH and fractions (300 mg/kg) andpeptide sequences (5 mg/kg) on systolic, diastolic and mean blood pressure was evaluated by telemetryon Spontaneously Hypertensive Rats (SHR), after single oral administration. Despite their ACE-inhibitoryeffect in vitro, neither WPH, Whey <3 kDa, Whey <1 kDa or peptide sequences exhibited antihyperten-sive activity. In addition, KGYGGVSLPEW was not only devoid of AT1receptor antagonism but, on thecontrary, had a similar effect to that of Ang II by facilitating the noradrenaline release from sympatheticnerve terminals. In vitro ACE blockade does not always correlate with antihypertensive activity and food-derived peptides cannot be classified as antihypertensive agents based exclusively on in vitro assays. Theabsence of an antihypertensive effect may also be a result of the interaction of these compounds withother components of the systems involved in the blood pressure control.